2009
DOI: 10.1038/mt.2009.56
|View full text |Cite
|
Sign up to set email alerts
|

Host and Vector-dependent Effects on the Risk of Germline Transmission of AAV Vectors

Abstract: The assessment of the risk of germline transmission of vector-coded sequences is critical for clinical translation of gene transfer strategies. We used rabbit models to analyze the risk of germline transmission of adeno-associated viral (AAV) vectors. Intravenous injection of AAV-2 or AAV-8 resulted in liver-mediated, long-term expression of therapeutic levels of human factor IX (hFIX) in a dose-dependent manner. In high-dose cohorts, AAV-8 resulted in twofold higher levels of circulating hFIX and of vector DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 37 publications
5
34
1
Order By: Relevance
“…This is consistent with the observation that AAV-6 gcn values were higher in the liver than those of AAV-5. The efficacy of the AAV-6 vectors is comparable and potentially superior (in the high-dose cohort) to AAV-8 vector, as has been previously reported using this model (Favaro et al, 2009).…”
Section: Efficacy and Safety Of Aav-5 And Aav-6 In Rabbitssupporting
confidence: 56%
See 3 more Smart Citations
“…This is consistent with the observation that AAV-6 gcn values were higher in the liver than those of AAV-5. The efficacy of the AAV-6 vectors is comparable and potentially superior (in the high-dose cohort) to AAV-8 vector, as has been previously reported using this model (Favaro et al, 2009).…”
Section: Efficacy and Safety Of Aav-5 And Aav-6 In Rabbitssupporting
confidence: 56%
“…Previous data demonstrated that the duration of detectable vector sequences in the semen of rabbits injected with AAV-2 and AAV-8 was vector dose-dependent (Favaro et al, 2009). Here we documented similar findings for AAV-6.…”
Section: Clearance Of Aav Sequences In Semen Is Faster In Rabbits Injmentioning
confidence: 99%
See 2 more Smart Citations
“…15 These data suggested that the presence of vector DNA in the semen was transient and that the risk of observing this was dose-related. 16,17 The trial was therefore modified to include a recommendation to bank sperm in advance of the procedure for those considering fathering additional children, and a recommendation that participants use barrier birth control until 2 sequential semen specimens were negative by PCR for vector sequences (Table 1). Subsequent clinical studies have confirmed the animal data, and there have been no cases of semen being persistently positive for vector sequences after administration of either AAV2 or AAV8 vectors.…”
Section: Problems Identified In the First Aav-fix Trialmentioning
confidence: 99%